Chicken telomerase reverse transcriptase promotes the tumorigenicity of avian leukosis virus subgroup J by regulating the Wnt/β-catenin signaling pathway - Yong Xiang; Canxin Liang; Qingbo Li; Qinxi Chen; Yang Zhou; Xiaoxue Zheng; Di Zhou; Zepeng Wang; Guyao Wang; Weisheng Cao (Veterinary Research, 2022)
Abstract This research aimed to analyze the regulatory effect of chicken telomerase reverse transcriptase (chTERT) on the Wnt/β-catenin signaling pathway and its effect on the tumorigenicity of avian leukosis virus subgroup J (ALV-J) through in vivo experiments. The chTERT eukaryotic expression plasmid and its recombinant lentivirus particles were constructed for in vivo transfection of chTERT to analyze the effect of chTERT continuously overexpressed in chickens on the tumorigenicity of ALV-J. During 156 days of the artificial ALV-J tumor-inducing process, 7 solid tumors developed in 3 chickens in the chTERT-overexpression group (n = 26*2) and no tumors developed in the control group (n = 26*2). Another 18 tumors induced by ALV-J were confirmed and collected from breeding poultry farms. And we confirmed that chTERT was significantly highly expressed in ALV-J tumors. The ELISA data suggested that the protein levels of β-catenin and c-Myc in the chicken plasma of the chTERT-overexpressing group with ALV-J infected were consistently and significantly higher than those of the control group. Compared with that of the tumor-adjacent tissues, the activity of the Wnt/β-catenin signaling pathway and expression of the c-Myc was significantly increased in ALV-J tumors. And the percentage of apoptosis in ALV-J tumors significantly lower than that in tumor-adjacent tissues. Immunohistochemistry, Western blot and RT-qPCR suggested that the replication level of ALV-J in tumors was significantly higher than that in tumor-adjacent tissues. This study suggests that chTERT plays a critical role in the tumorigenicity of ALV-J by enhancing the Wnt/β-catenin signaling pathway, which will contribute to further elucidating the tumor-inducing mechanism of ALV-J.